2019
DOI: 10.1016/j.dib.2019.104310
|View full text |Cite
|
Sign up to set email alerts
|

Data from a three-wave complete longitudinal design survey on career calling and related constructs (N = 6368)

Abstract: This dataset provides de-identified raw responses to a non-anonymous three-wave online survey with a 12-month time lag. Data collection was part of a larger project on the development of career calling in Italian college students. The first wave was collected during the fall of 2014. Participants were bachelor's or master's students enrolled in 24 different study domains and 4 different universities. Sample sizes for each wave are N T 1 = 5,886, N T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…We argue that calling follows the same developmental process that Maslow theorized for self-actualization and self-transcendence: The more the individuals feel that they are living out a calling, the more they build on and understand their calling, which in turn strengthens their motivation and their efforts to live it out, in a cyclical process that ultimately leads to profoundly meaningful and self-transcendent activities. 1 This hypothesis is supported by the evidence that the relation between a calling and its positive outcomes is stronger when individuals are living out their calling: Living out a calling both mediates and moderates the impact of perceiving a calling’s meaning in work and life, work and life satisfaction, career commitment, and maturity (Dalla Rosa et al, 2017; Duffy et al, 2013; Duffy, Bott, Allan, Torrey, & Dik, 2012; Duffy & Dik, 2013). Comparing academics with an unanswered occupational calling to academics who were actually living out their calling and academics with no calling at all, Gazica and Spector (2015) found that the former group reported significantly poorer physical and psychological health.…”
Section: The Construct Of Callingmentioning
confidence: 97%
See 1 more Smart Citation
“…We argue that calling follows the same developmental process that Maslow theorized for self-actualization and self-transcendence: The more the individuals feel that they are living out a calling, the more they build on and understand their calling, which in turn strengthens their motivation and their efforts to live it out, in a cyclical process that ultimately leads to profoundly meaningful and self-transcendent activities. 1 This hypothesis is supported by the evidence that the relation between a calling and its positive outcomes is stronger when individuals are living out their calling: Living out a calling both mediates and moderates the impact of perceiving a calling’s meaning in work and life, work and life satisfaction, career commitment, and maturity (Dalla Rosa et al, 2017; Duffy et al, 2013; Duffy, Bott, Allan, Torrey, & Dik, 2012; Duffy & Dik, 2013). Comparing academics with an unanswered occupational calling to academics who were actually living out their calling and academics with no calling at all, Gazica and Spector (2015) found that the former group reported significantly poorer physical and psychological health.…”
Section: The Construct Of Callingmentioning
confidence: 97%
“…Indeed, it has been found that people who feel called to a career or domain are passionate about the calling domain ( passion component : Bunderson & Thompson, 2009; Dobrow & Tosti-Kharas, 2011; Hagmaier & Abele, 2012; Wrzesniewski et al, 1997), have a purpose in life ( purposefulness component : Dik & Duffy, 2009; Dobrow & Tosti-Kharas, 2011; Praskova et al, 2015), sacrifice other areas of their life in favor of their calling ( sacrifice component : Bunderson & Thompson, 2009; Dobrow & Tosti-Kharas, 2011), feel that the calling’s domain is always on their mind ( pervasiveness component : Dobrow & Tosti-Kharas, 2011; Hagmaier & Abele, 2012; Wrzesniewski et al, 1997), report that their calling comes from something greater than or beyond them ( transcendent summons component : Dik & Duffy, 2009; Hagmaier & Abele, 2012; Hunter, Dik, & Banning, 2010; Zhang, Dik, Wei, & Zhang, 2015; Zhang, Herrmann, Hirschi, Wei, & Zhang, 2015), and that part of their calling is being useful to others ( prosocial orientation component : Bunderson & Thompson, 2009; Dik & Duffy, 2009; Hagmaier & Abele, 2012; Praskova et al, 2015). In terms of outcomes, it has been repeatedly shown that having a calling fosters commitment and engagement with the calling’s domain and that individuals with a calling are more satisfied with their job and their life (see, e.g., Dalla Rosa, Galliani, & Vianello, 2017; Dobrow & Tosti-Kharas, 2011; Duffy et al, 2013; Hagmaier & Abele, 2012, for a review).…”
Section: The Construct Of Callingmentioning
confidence: 99%
“… 1 The exceptions are Dalla Rosa, Galliani, and Vianello’s (2017) book chapter and Rowles, Cox, and Pool’s (2021) commentary article, which meta-analyzed a select group of studies (as opposed to those derived via systematic search) and/or a limited number of variables in relation to calling. …”
mentioning
confidence: 99%
“…Scores on the calling scale showed good internal consistency (α = 0.93) and measurement invariance across time and study domains. The UMCS showed convergent validity with both the CVQ-presence scale (Dik et al, 2008) that measures perceiving a calling ( r =.72, Dalla Rosa et al, 2019b), a single-item measure of living a calling ( r =.58, Vianello et al, 2020), and the living a calling scale by Duffy et al (2012; r (348) =.78, Dalla Rosa & Vianello, 2021; r (152) =.73, Vianello & Dalla Rosa, 2020). Example items are “I am passionate about my work,”“I believe that I have been called to pursue my current line of work,” and “My work helps me live out my life’s purpose.” The original scale is composed of 22 items, in this study we used a longer version of the UMCS composed of 28 items.…”
Section: Methodsmentioning
confidence: 94%